2017
DOI: 10.18203/2319-2003.ijbcp20174786
|View full text |Cite
|
Sign up to set email alerts
|

Perception of doctors towards Adverse Drug Reaction (ADR) reporting: a cross sectional survey using a validated questionnaire

Abstract: Background: Several studies have shown lack of sufficient knowledge and awareness among doctors on ADR reporting. Knowledge and attitude of doctors about ADR greatly influences extent of reporting. Identifying factors affecting ADR-reporting is vital to enable Pharmacovigilance teams to implement interventions to enhance rate and quality of reporting of ADRs. Hence, this study is done to evaluate perceptions of doctors towards ADR-reporting and to determine barriers for reporting ADR.Methods: Cross sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
4
5
1
Order By: Relevance
“…However, reporting rates in this study are appreciably lower than seen in India where 47% of respondent physicians had reported an ADR [71] and Malaysia where 51.9% of physicians and pharmacists in PHC facilities had reported an ADR in the past year [19]. Whilst the majority of HCPs surveyed (89.0%) felt that ADR reporting is a professional obligation ( Table 2) similar to other countries [17,19,56,71,74,76], they would be encouraged to report ADRs if the reaction is serious (89.5%), for a new product (89.5%) or unusual (78.0%) ( Fig. 1), similar to other studies [75][76][77].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…However, reporting rates in this study are appreciably lower than seen in India where 47% of respondent physicians had reported an ADR [71] and Malaysia where 51.9% of physicians and pharmacists in PHC facilities had reported an ADR in the past year [19]. Whilst the majority of HCPs surveyed (89.0%) felt that ADR reporting is a professional obligation ( Table 2) similar to other countries [17,19,56,71,74,76], they would be encouraged to report ADRs if the reaction is serious (89.5%), for a new product (89.5%) or unusual (78.0%) ( Fig. 1), similar to other studies [75][76][77].…”
Section: Discussioncontrasting
confidence: 81%
“…Whilst a positive attitude to ADR reporting existed among HCPs working at PHC facilities in our study, the actual practice of ADR reporting was poor, similar to studies in other LMICs including India [57,[69][70][71][72][73], Pakistan [54] and Romania [74].…”
Section: Discussionsupporting
confidence: 70%
“…15 86.36% of participants of the present study stated that reporting by one person can make a significant difference to community (Table 2 ) different from study done by Khan et al, (16.2%), similar to study done in clinicians in by Kunnoor et al(83%). 8,13 Most of the post graduate students suggested that there should be an ADR reporting center in the OPD complex of the hospital (86.36% ) in a study done among prescribers by Radhakrishna et al, and ADR monitoring center should be in every hospital. 14 This is in accordance with study done in nurses by Radhakrishna et al, and Gupta et al, in South India (74.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The results were similar to a study showing that nearly one-fourth didn't report fearing legal liabilities, difficulty diagnosing ADR and negative impact on doctors. 11 In this study, all of medical professionals are ignorant of various aspects of pharmacovigilance and adverse drug reactions. When the KAP scores were compared between the groups nurses scored lesser than doctors and PG's.…”
Section: Discussionmentioning
confidence: 99%
“…This was in contrast to results seen in other studies showing where doctors had a better knowledge. [9][10][11] 98% of doctors and 96% of nurses have experienced ADR in their professional practice but reporting of such ADR to the PhV centre was 38% in doctors, 24% in PG's and 15% in nurses, which is significantly less compared to the occurrence of ADR's. Similar results were seen in the study conducted by Palaian et al, 70.8% of the health care providers (doctors, nurses and pharmacists) felt that ADR reporting should be made mandatory and a study showed only 15% of respondents had reported an ADR previously.…”
Section: Discussionmentioning
confidence: 99%